Hemolytic Diseases - Odilova shaxnoza (Zien Journals, 2022)
Hemolytic anemia is a condition where red blood cells disappear faster than they can be produced. The destruction of red blood cells is called hemolysis. This article discusses this disease thoroughly
Keywords: hemolytic anemia; oxygen; hereditary